Pelatihan Budidaya Dalam Ember (Budikdamber) Kepada Peserta Didik Madrasah Aliyah Muhammadiyah Purwokerto - Muhammad Azharul Rijal (Fakultas Pertanian_Universitas Tidar, 2025)
Environmentally friendly aquaculture for effective fish production is currently urgently needed by the community. Aquaculture develops every year according to the dynamics of market needs and demands as well as optimal fishing. For this reason, it is necessary to develop integrated aquaculture cultivation that is able to complement the needs of protein from fish for the community. Students or students as the younger generation have a strategic role as a group capable of making changes. As part of the agents of change in society, the role of students as fish cultivators can be increased for the benefit of talent and specialization, coaching, training and service to the community. The development of aquaculture can act as an entry point for the growth of other businesses related to aquaculture. The feed industry, cultivation facilities and infrastructure can develop around the area, especially urban areas or cultivation centers. Agricultural/fishery extension agents can enter through this activity to improve technical services. Likewise, elements of higher education as coaches of students in schools to develop talents and agents of change in society. Service activities use the direct participation method by hatching catfish which includes: providing cultivation material with lectures followed by discussions, implementing cultivation with direct practice at partners' places, coaching and mentoring.